2018
DOI: 10.30657/pea.2018.19.05
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining of biomorphic composites based on carbon materials

Abstract: Aim of this paper is to present the properties of carbon preforms for the production of biomorphic composites. Carbon samples were obtained through pyrolysis of paulownia wood, replicating the microstructure of the cellulosic precursor. Many characterization methods such as Raman Spectroscopy, light microscopy, hardness tests and pore size analyzer detection were used to investigate the microstructure of the product as well as the pore size of carbon samples. Obtained results showed that the parts of early or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The modulus of rupture and modulus of elasticity are 29 MPa and 3970 MPa, respectively [10]. However, Paulownia species have a very soft wood (10-25 MPa on Janka's scale) [11].…”
Section: Discussionmentioning
confidence: 99%
“…The modulus of rupture and modulus of elasticity are 29 MPa and 3970 MPa, respectively [10]. However, Paulownia species have a very soft wood (10-25 MPa on Janka's scale) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Type of carbon precursor is one of important process parameter in graphite production. Generally, carbon rich material such as coke and coal tar pitch are utilized (Lisiecka et al, 2018). However, contemporary research has been shifted toward greener and sustainable option, such as biomass waste (Paun et al, 2016;Slovaca and Cehl, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Oxytree wood is utilized in construction or furniture-making [14]. Paulownia clon in Vitro 112 ranks as class I on Janka’s hardness scale—very soft wood [15]. It has been shown that the biochar from Paulownia produced at 600 °C is a pure carbon without organic composition, characterized by a pore size from 35.8 to 290.5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the biochar from Paulownia produced at 600 °C is a pure carbon without organic composition, characterized by a pore size from 35.8 to 290.5 μm. Such material, after proper treatment, can be applied as a filtration agent or catalyst [15]. Oxytree can also be utilized for energy purposes.…”
Section: Introductionmentioning
confidence: 99%